2008
DOI: 10.1007/s00467-008-0857-3
|View full text |Cite
|
Sign up to set email alerts
|

Obstacles to the prescribing of growth hormone in children with chronic kidney disease

Abstract: Despite its effectiveness, recombinant human growth hormone (rhGH) is under-utilized in short children with chronic kidney disease (CKD). We conducted a multicenter study to explore the obstacles preventing children with CKD from receiving rhGH. We investigated the use of rhGH in 307 children with CKD from seven pediatric nephrology centers. Among the 110 patients who fell below the 5th percentile, 56 (51%) had not received rhGH. The most common reasons given for these children not receiving rhGH were family r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 13 publications
1
16
0
1
Order By: Relevance
“…In our study, children with short stature had a higher prevalence of Medicaid use, which may be a marker of lower socioeconomic status that could partially explain the higher mortality risk in shorter children despite transplantation. Other factors such as nonadherence to therapy and lower access to care, which are commonly associated with short stature in children with CKD (19)(20)(21), may also be underlying factors that could contribute to the elevated mortality risk in children with short stature.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, children with short stature had a higher prevalence of Medicaid use, which may be a marker of lower socioeconomic status that could partially explain the higher mortality risk in shorter children despite transplantation. Other factors such as nonadherence to therapy and lower access to care, which are commonly associated with short stature in children with CKD (19)(20)(21), may also be underlying factors that could contribute to the elevated mortality risk in children with short stature.…”
Section: Discussionmentioning
confidence: 99%
“…40 The demand for daily injections and psychosocial factors are associated with low rGH use. [52][53][54] Children may reach normal final adult height if started on rGH therapy at an early age. Response to rGH therapy may vary.…”
Section: Recombinant Growth Hormone Therapy In Ckdmentioning
confidence: 99%
“…A recent report generated from a medical record review demonstrated that a rationale to explain the non-utilization of rhGH was not found in a substantial percentage of untreated patients [12]. Pertinent issues that may contribute to this poor utilization include the complexity of general CKD care, the need for longterm, daily rhGH injections, and difficulties with insurance authorization.…”
Section: Discussionmentioning
confidence: 99%